Fear increases likelihood of seeking decisional support from others when making decisions involving ambiguity. (16th November 2021) - Ferrer, Rebecca A.; Ellis, Erin M.; Orehek, Edward; Klein, William M. P.
Abstract: Individuals often turn to others for decision‐making advice, which has the potential to improve decision‐making outcomes when advice is drawn from a reliable source. Because seeking advice is a kind of information seeking, it is likelier to occur when decisions involve ambiguity or when full information about outcomes is unavailable. We examined whether experimentally induced incidental fear, known to increase information seeking, increased intentions to seek decision‐making advice and whether this effect was stronger for decisions involving ambiguity. In Study 1, fear increased the likelihood of seeking advice about an ambiguous decision in which both options carried some risk, compared to neutral emotion (and anger). In Study 2, a 2 (emotion) by 2 (minimal vs. extensive information) design, fear increased the likelihood of seeking advice about palliative care only after a simple definition of palliative care (minimal information), but not after more comprehensive (extensive) information about its nature, benefits, and efficacy. These findings suggest that incidental fear may encourage people to seek advice about decisions involving ambiguity or when full information to make the decision is not available.